Countering violent extremism through public health practice : proceedings of a workshop (The National Academies Press, 2017)
Countering violent extremism consists of various prevention and intervention approaches to increase the resilience of communities and individuals to radicalization toward violent extremism, to provide nonviolent avenues for expressing grievances, and to educate communities about the threat of recruitment and radicalization to violence. To explore the application of health approaches in community-level strategies to countering violent extremism and radicalization, the National Academies of Sciences, Engineering, and Medicine held a public workshop in September 2016. Participants explored the evolving threat of violent extremism and radicalization within communities across America, traditional versus health-centered approaches to countering violent extremism and radicalization, and opportunities for cross-sector and interdisciplinary collaboration and learning among domestic and international stakeholders and organizations. This publication summarizes the presentations and discussions from the workshop.